Networked Curricula: Fostering transnational partnerships in open and distance education and blended learning - Ubachs, George (Proceedings of the International Conference on Networked Learning, 2012)
The general aim of the NetCU project is to develop models, guidelines and strategies for transnational networked curricula that supply a broader range of content and learning activities, supported by innovative ICT. This is done in a series of actions: As a first step a comprehensive overview of existing networked curricula was drawn and presented in an on-line map. A set of key areas on networked curricula were analysed, e.g. the educational model, the ways of sharing of content, the role of mobility, issues of assessment, recognition and quality assurance, language provision, the role and usage of ICT in the curriculum, its management and business model. Which advantages has the curriculum for the partners and which obstacles were/are faced? How do the students embrace it? How are the national, legal and institutional frameworks defined. Information on these and further questions will deliver comprehensive data for deriving systematic models of networked curricula in ODE and blended learning. The analyses of existing models has led to a publication of a handbook on networked curricula. The models of specific cases were transferred into common features of networked curricula in ODE and blended learning and translated into viable guidelines for developing and implementing transnational networked curricula. To strengthen the important technological dimension of networked curricula in ODE and blended learning innovative ICT solutions were shared, analysed and plugged into one of the case studies for testing and enhancing. The results achieved will stimulate and facilitate the set-up of new networked curricula and improve existing ones and thus trigger the positive effects as described in the previous part of this document. In this paper presentation we will address the success factors identified in the analysed 19 networked curricula, the definition of models in networked curricula as well as the support offered by the ICT toolbox on social media and learning platforms.